Factors associated with Turkish individuals’ purchase of transportation, accommodation, and household services from digital platforms - Hatice Nur Yıldız; İbrahim Yıldız; Ömer Alkan (PLoS ONE, 2026)
Digital platforms are technological applications with steadily increasing popularity. This study aims to investigate various factors associated with the purchase of transportation, accommodation, and household services via digital platforms by individuals in Türkiye. This study used the 2023 “Household Information Technologies Usage Survey Microdata Set” provided by the Turkish Statistical Institute. To identify the possible effects of factors such as gender, education level, age, income level, and household size on digital platforms, binary logistic regression analysis was used. According to the study’s results, all the factors, including gender, education level, age, income level, and household size, may affect the use of digital platforms. Accordingly, the likelihood of using digital platforms is higher among men compared to women, younger individuals compared to older ones, and individuals with higher education and income compared to those with lower levels. In terms of household size, a negative relationship was found. In other words, individuals from larger households are less likely to use digital platforms. The study’s findings suggest that beliefs and values, consumption habits, social roles and responsibilities, and the factor of trust in digital platforms play a role in the use of digital platforms. In the study, which includes evaluations that digital platforms will become increasingly widespread in Türkiye, where Western values and a modern lifestyle are gradually becoming more prevalent, recommendations are made regarding the perception and promotion of digital platforms and the importance of public relations practices.